Study of micro particles deposition in ribbed channel: A numerical investigation in turbulent airflow. (7th April 2014) - Samimi, Kianoosh; Sharafi, Helia; Padayodi, Essolé; Bahrani, Seyed Amir
<x content-type="archive" xml:space="preserve">Abstract</x> The air is modeled as incompressible flow in a ribbed channel. The existence of ribs on channel surface causes the turbulence in flow, therefore we must solve the turbulence equations. There are previous experimentally investigations on turbulence flow in ribbed channels. In this article, the results of numerical simulation are compared with experimental results and the effectiveness of k−ε model in solving the problem of micro-particle deposition with Lagrangian model is studied because of complexities of turbulent flow, the problem is modeled both 2- and 3-dimensionally. After solving the fluid domain, the particle equations of motion are solved separately and finally the particle deposition on channel surface is calculated. Considering the physic and complications of turbulent flows, the results of 2-D simulation are different with experimental results, despite of 3-D results, which are in complete accordance with experimental results.